Single staged repair of an anastomotic tracheal fistula following Mckeown esophagectomy via cervical incision: a case report - Haoqian Zheng; Chenyang Guo; Yadi Zhang; Hang Gu; Yinzhi Zhao; Run Xiang; Wei Dai; Xing Wei; Tianpeng Xie; Qiang Li; Xiang Wang (Journal of Cardiothoracic Surgery)
Abstract Background The incidence of tracheoesophageal fistula (TEF) following esophagectomy is less than 3%, but it often leads to severe complications and can even be life-threatening to patients. Surgical repair methods for TEF include muscle or omental flap support, biologic patch repair, and sleeve resection. In recent years, there has been an increasing number of case reports on primary closure via a cervical incision, with a rising success rate and a lower incidence of postoperative complications. Case presentation A case is presented involving a 68-year-old female patient with esophageal squamous cell carcinoma who underwent thoracoscopic McKeown esophagectomy combined with gastric conduit reconstruction. On postoperative day 10, the patient presented with severe coughing. Gastroscopy and bronchoscopy confirmed a tracheoesophageal fistula at the anastomotic site. After 2 weeks of anti-infective therapy, drainage, and nutritional support, the fistula persisted. Subsequently, an exploratory surgery was performed via the original cervical incision, and the fistula was repaired with primary suture. The patient received routine dressing changes and continued anti-infective therapy postoperatively. One week later, gastroscopy and bronchoscopy revealed complete healing of the trachea, with closure of the anastomotic fistula, and no abnormalities were detected upon oral intake. Conclusion This case demonstrates that in patients identified early, with complete drainage, adequate anti-infection measures, and improved nutritional status, primary closure of the tracheoesophageal junction through the original cervical incision can successfully treat an anastomotic trachea-fistula following esophagectomy. Our report details the process of primary repair of TEF through the cervical approach, contributing additional references to existing literature.